Analisis Pembebanan dan Ketidakseimbangan Beban pada Penentuan Susut Umur Transformator Distribusi - Anggy Eri Sodilesmana; Nasrulloh Nasrulloh; Rizki Noor Prasetyono (Journal of Electronic and Electrical Power Applications, 2021)
Transformer life can be reduced due to several things. One of the causes of reduced age is loading. Loading causes an increase in the temperature of the transformer. The aging of this insulation is so fast if the insulation operates in temperatures that exceed the permissible limits, namely at a Hot Spot temperature of 98°C. If a transformer experiences a Hot Spot temperature of 98°C, then its life shrinkage will be so fast that it can reduce the expected life of the transformer. The type of research used is descriptive quantitative research to describe the effects of loading on the transformer. From the results of the study, the percentage of unbalance transformer loads with 100 kVA and 200 kVA TRAFINDO brands did not meet the standards because the percentage value was more than 20%. The results of the analysis of the calculation of life loss and the remaining life of all transformers that are burdened above 80% are still normal or have little effect on the life of the transformer and the estimated remaining life is still above 20 years. So, all transformers operating at PT. PLN (Persero) Rayon Bumiayu is still by the standard.